Exploring The Difficulty Level of Arabic Language Questions in The Fahmil Qur’an Book: The Key to Developing Students' Critical Thinking - Abdurrauf Abdurrauf; Dewi Chamidah (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2025)
Research on the contribution of Musabaqah Fahmil Qur'an (MFQ) materials to developing critical thinking skills remains limited, particularly regarding its Arabic language questions. This study analyses the role of Arabic questions in the 2022 MFQ guidebook in enhancing the critical thinking skills of university students, focusing on the El-Faqih community at UIN Malang. Using a descriptive qualitative approach, data were collected through Arabic tests and critical thinking questionnaires based on Angelo's framework. The results reveal that MFQ questions are designed with a scaffolded difficulty level, peaking in the final round. This structure effectively stimulates higher-order thinking skills, such as interpreting, analysing, and evaluating Qur'anic content. The findings confirm that MFQ significantly sharpens critical thinking. Therefore, educators and competition organisers should design questions that promote deeper cognitive engagement. Further research is recommended to explore additional pedagogical strategies to maximise MFQ's critical thinking benefits.